Beyond the quantum - Nieuwenhuizen, Theo M. (World Scientific, 2007)
Already Einstein could never see quantum mechanics as a complete theory. Nowadays, many researchers, including 't Hooft, view quantum mechanics as a statistical description of some underlying reality. The workshop "Beyond the Quantum", organized in Spring 2006 at the Lorentz Center in Leiden, The Netherlands, was one of the first meetings completely devoted to physics that may need an explanation beyond quantum mechanics. A broad variety of subjects was covered. The present book reflects this.
Keywords: Quantum theory.; Physics -- Philosophy.; Science -- Philosophy.; Théorie quantique.; Physique -- Philosophie.; SCIENCE -- Physics -- Quantum Theory.; Physics -- Philosophy; Quantum theory; Science -- Philosophy